BULLYING NA ESCOLA - Mariana Aparecida Grillo; Ana Caroline Silva Santos (Universidade do Oeste Paulista, 2015)
This article intends to conduct an analysis and reflection of one of the important issues which it is education: bullying, because it is a violence that occurs in the school of repetitive and deliberate manner in which its consequences can cause damage significant to emotional training, psychological and socio-educational of the victim, if the student. Note that bullying is increasing in epidemic form in schools and its effects are traumatizing students to witness and those who suffer the action, because it is violence with deliberate and repetitive character. In terms of overall objective, conduct yourself will this article in order to obtain information about bullying in the school environment, more specifically will address: The Bullying conceptions; Investigate the causes and consequences can be seen in the behavior of students; To study the key players of Bullying in school. Thus, it is a qualitative methodological approach that will make the use of literature by various authors for the issue of deepening. It resulted contribute in the actions of professionals in the face of violence. Therefore, it is concluded that the school is a place of learning, where change is necessary, both in order to act as the thinking of people and students.